(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In the current study, an effort has been made to stabilise the local expansionary soils using the appropriate mix of locally accessible industrial waste with or without lime. In this study, a sample of high expansive soils was employed taken from Rajpura (PB) and a sample of low expansion soils. Industrial waste like fly ash and wool from local businesses are utilised as additions to stabilise soil both. Fly ash and wool waste are individually added to soils with varying quantities (from 5 to 30 percent) and the weight of a dry soil blend increases by 5 percent. The geotechnical qualities of solar mixes are examined by a range of experiments such as CBR, unconfined compression, triaxial compression and consolidation tests. After 9 days of water treatment, the uncontained compression and triaxial compressive tests are performed on the soil-fly ash and soil-wool waste samples. The samples of soil-fly ash and soil-wool waste are shown to reduce the plasticity, swelling and compressibility by increasing additives and increasing matching CBR, shear strength and permeability.